2006
DOI: 10.1097/01.sap.0000222571.98387.71
|View full text |Cite
|
Sign up to set email alerts
|

Hair-Thread Tourniquet Syndrome in an Infant With Bony Erosion

Abstract: Hair-thread tourniquet syndrome is a rare condition where appendages are strangulated by an encircling strand of hair, a thread, or a fiber. The condition usually occurs in very young patients in the first few months of life. We present a unique case of a 3-month-old baby girl with hair-thread tourniquet syndrome in whom a hair cheese-wired through the skin and soft tissue of the toe and caused bony erosion of the underlying phalanx. An extensive literature review and meta-analysis of the topic are also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 55 publications
0
30
1
3
Order By: Relevance
“…According to the literature, hair-thread tourniquet syndrome occurs in boys but some studies have reported this syndrome in girls (8). Circumcision, lack of cleanliness, a moist environment, and childhood are important predisposing factors (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, hair-thread tourniquet syndrome occurs in boys but some studies have reported this syndrome in girls (8). Circumcision, lack of cleanliness, a moist environment, and childhood are important predisposing factors (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews have reported HTTS as affecting the following structures:digits (hand digits (24–47%) [4, 5], toes (25–43%) [4, 5]); external genitalia (penis (44%) [1, 6], Clitoris (6%) [3, 4, 7], labia [8]), head and neck (tongue, uvula, and neck [quoted from Saad et al [6]]). …”
Section: Typical Characteristics Of Htts Presentationmentioning
confidence: 99%
“…[2] Diğer nadir turnike sendromları dil, uvula ve boyunda tanımlanmıştır. [3] Literatürde ilk defa McNeal 1987 yılında "Clinical Pediatrics" dergisinde uvulaya saç telinin dolanması ile turnike sendromunu uvulada tanımlamıştır. [4] McNeal bu olgu sunumunda, vücut uzantılarının saç teli ile strangulasyonunun kaza sonucu gelişebileceğini rapor etmiştir.…”
Section: Uvula öDeminin Nadir Bir Nedeni Mi? Yoksa Uvula Turnike Sendunclassified